Lipid droplets in Arabidopsis thaliana leaves contain myosin-binding proteins and enzymes associated with furan-containing fatty acid biosynthesis - Omata, Yuto; Sato, Reina; Mishiro-Sato, Emi; Kano, Keiko; Ueda, Haruko; Hara-Nishimura, Ikuko; Shimada, Takashi L. (Frontiers in Plant Science, 2024)
Lipid droplets (LDs) are lipid storage organelles in plant leaves and seeds. Seed LD proteins are well known, and their functions in lipid metabolism have been characterized; however, many leaf LD proteins remain to be identified. We therefore isolated LDs from leaves of the leaf LD–overaccumulating mutant high sterol ester 1 (hise1) of Arabidopsis thaliana by centrifugation or co-immunoprecipitation. We then performed LD proteomics by mass spectrometry and identified 3,206 candidate leaf LD proteins. In this study, we selected 31 candidate proteins for transient expression assays using a construct encoding the candidate protein fused with green fluorescent protein (GFP). Fluorescence microscopy showed that MYOSIN BINDING PROTEIN14 (MYOB14) and two uncharacterized proteins localized to LDs labeled with the LD marker. Subcellular localization analysis of MYOB family members revealed that MYOB1, MYOB2, MYOB3, and MYOB5 localized to LDs. LDs moved along actin filaments together with the endoplasmic reticulum. Co-immunoprecipitation of myosin XIK with MYOB2-GFP or MYOB14-GFP suggested that LD-localized MYOBs are involved in association with the myosin XIK–LDs. The two uncharacterized proteins were highly similar to enzymes for furan fatty acid biosynthesis in the photosynthetic bacterium Cereibacter sphaeroides, suggesting a relationship between LDs and furan fatty acid biosynthesis. Our findings thus reveal potential molecular functions of LDs and provide a valuable resource for further studies of the leaf LD proteome.